2020
DOI: 10.1111/aos.14715
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic and aberrometric assessment of first‐time diagnosed paediatric keratoconus based on age ranges: a multicentre study

Abstract: Purpose To describe paediatric keratoconus (KC) patients by tomographic and aberrometric characteristics at first diagnosis, in a multicentre study. Methods We included 278 eyes from 139 paediatric patients, with a first tomographic diagnosis (Pentacam®) of KC prior to 18 years old. KC classification was based on the KC Index (≥ 1.07) and Topographic Keratoconus Classification (TKC ≥ 1). Patients were divided based on age ranges (14 and under and over 14 years) and gender. Statistical analysis was performed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
1
12
2
Order By: Relevance
“…It has been reported that nearly half of the pediatric keratoconus cases present with progressive disease, which is more aggressive than in adult patients ( 13 , 17 ). Therefore, the distribution of pediatric keratoconus, which is in the early stages of the disease, has been reported inadequately but is of great value, especially in different age and gender groups ( 18 , 19 ). A recent multicenter study of pediatric keratoconus showed that the age was not different between male and female patients, with female patients exhibiting a higher topographic keratoconus classification (TKC) value than male patients ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that nearly half of the pediatric keratoconus cases present with progressive disease, which is more aggressive than in adult patients ( 13 , 17 ). Therefore, the distribution of pediatric keratoconus, which is in the early stages of the disease, has been reported inadequately but is of great value, especially in different age and gender groups ( 18 , 19 ). A recent multicenter study of pediatric keratoconus showed that the age was not different between male and female patients, with female patients exhibiting a higher topographic keratoconus classification (TKC) value than male patients ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the top 10 parameters from that list (see Table S1 ), 6 nonredundant, potentially platform-independent parameters were selected: age, known to affect KC progression [ 11 , 26 ]; the average keratometry in a 3 mm area around the maximum keratometry (KmaxZonalMean3mm) [ 27 ]; the steepest radius (RsF) and best fit sphere over an area of 8 mm (BFSF) of the front surface; and the average radius of the back surface (RmB) and LOGIK [ 18 ], which is based on the elevation maps of both corneal surfaces and the minimum pachymetry. None of the parameters included were based on a single corneal point.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis often requires an assessment of the topography and/or tomography of the cornea to reveal subtle changes in corneal morphology. [3][4][5][6] The evaluation of corneal topography and tomography may itself be challenging and open to misinterpretation. 5 Several indices have been proposed to facilitate differentiation between keratoconus and normal eyes, such as the zone of increasing corneal power, inferiorsuperior corneal power asymmetry, steepest radial axes, posterior and anterior ectasia and corneal pachymetry.…”
Section: Introductionmentioning
confidence: 99%